2020
DOI: 10.7759/cureus.8346
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19): Forecast of an Emerging Urgency in Pakistan

Abstract: Background/Aims Novel coronavirus disease 2019 (COVID-19) is a global challenge due to little available knowledge and treatment protocols. Thus, there is a great need for collecting data related to COVID-19 from all around the world. Hence, we conducted this study, collecting daily data on COVID-19, to map the epidemiology outbreak and forecast its trajectory for May 2020. Methodology The data was collected from the officially released reports of the National Institute of Health (NIH), Pakistan, and the World … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Machine learning algorithms exhibit many pros and cons, which are described in Table 3. [19,22,26,30,31] Genetic programming [30][31][32][33][34] Simple moving average [23] Other models [35] SEIR [12,36] Exponential models Logistic growth model [24,37,38] Flower pollination algorithm [29] SIRD [13,14] Deep learning Long short-term memory (LSTM) networks [25] Polynomial Neural Network [39] Neural network [31,40] Ecological Niche models [41] Regression methods [42][43][44] Prophet algorithm [45] Phenomenological model [46] Other models Adaptive neurofuzzy inference system [29] Regression tree algorithm [22] Support vector machine [39,47] Iteration method [48] Support vector Kuhntucker [47] 10…”
Section: Strengths and Weaknesses Of Forecasting Modelsmentioning
confidence: 99%
“…Machine learning algorithms exhibit many pros and cons, which are described in Table 3. [19,22,26,30,31] Genetic programming [30][31][32][33][34] Simple moving average [23] Other models [35] SEIR [12,36] Exponential models Logistic growth model [24,37,38] Flower pollination algorithm [29] SIRD [13,14] Deep learning Long short-term memory (LSTM) networks [25] Polynomial Neural Network [39] Neural network [31,40] Ecological Niche models [41] Regression methods [42][43][44] Prophet algorithm [45] Phenomenological model [46] Other models Adaptive neurofuzzy inference system [29] Regression tree algorithm [22] Support vector machine [39,47] Iteration method [48] Support vector Kuhntucker [47] 10…”
Section: Strengths and Weaknesses Of Forecasting Modelsmentioning
confidence: 99%
“…The SMA model is defined as the unweighted mean of the previous data (in finance or in science & engineering) (Sprinthall and Fisk 1990). Example of application of simple moving average in COVID-19 could be found in (Chaudhry, Hanif et al 2020).…”
Section: Simple Moving Average (Sma)mentioning
confidence: 99%
“…Chakraborty and Ghosh (2020) presented a realtime forecast of confirmed COVID-19 cases for several countries as well as risk assessment of the novel COVID-19 for some affected territory using regression tree algorithm. A simple movingaverage approach was used by(Chaudhry, Hanif et al 2020) to predict COVID-19 confirmed cases in Pakistan (Chen, Chen et al 2020Cheng, Burcu et al (2020).…”
mentioning
confidence: 99%
“…So would the administration's help bundle, which is just digressively centered on modern quality, effectively rescue enterprises. Chaudhry et al, (2020).…”
Section: Investment and Capital Formationmentioning
confidence: 99%